2014
DOI: 10.1523/jneurosci.2513-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3ε and ζ Regulate Neurogenesis and Differentiation of Neuronal Progenitor Cells in the Developing Brain

Abstract: During brain development, neural progenitor cells proliferate and differentiate into neural precursors. These neural precursors migrate along the radial glial processes and localize at their final destination in the cortex. Numerous reports have revealed that 14-3-3 proteins are involved in many neuronal activities, although their functions in neurogenesis remain unclear. Here, using 14-3-3/ double knockout mice, we found that 14-3-3 proteins are important for proliferation and differentiation of neural progen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 50 publications
5
95
0
1
Order By: Relevance
“…However, we found an increase in the levels of δ-catenin in the 14-3-3 FKO mice (Figure 6). This is consistent with a recent study conducted in the neural progenitor cells of 14-3-3 deficient mice and may provide a potential molecular mechanism for 14-3-3-dependent regulation of actin dynamics and dendritic spines in post-mitotic neurons (53). …”
Section: Resultssupporting
confidence: 93%
“…However, we found an increase in the levels of δ-catenin in the 14-3-3 FKO mice (Figure 6). This is consistent with a recent study conducted in the neural progenitor cells of 14-3-3 deficient mice and may provide a potential molecular mechanism for 14-3-3-dependent regulation of actin dynamics and dendritic spines in post-mitotic neurons (53). …”
Section: Resultssupporting
confidence: 93%
“…The database link for eomesodermin homolog isoform 1 in Mus musculus. The pattern of immunostaining we obtained matched that from previous publications describing immunostaining in mouse telencephalon (Avila et al, 2014;Toyo-oka et al, 2014), the immunostaining we obtained with the rabbit polyclonal in this study, and the immunostaining we had obtained from other Tbr2 antibodies in previous publications (Noctor et al, 2008;Cunningham et al, 2013b).…”
Section: Antibody Characterizationsupporting
confidence: 85%
“…This signal may represent the C-terminal fragment of Ca V 1.2, which functions as a calcium channel associated transcription regulator (Gomez-Ospina et al, 2006). 14-3-3ε, a signaling protein involved in neuronal migration and synaptic plasticity, was diffusely distributed in the cytoplasm both at P0 and P28 in neurons and astrocytes (Toyo-oka et al, 2014) (Figures 2K and 2L). FMRP, a polyribosome-associated RNA-binding protein that regulates translation of a large number of mRNAs (Contractor et al, 2015), was found in puncta, which likely reflect FMRP-associated mRNA granules, in the soma as well as dendrites in pyramidal neurons at P7 and P28 (Figures 2M, 2N and S5D).…”
Section: Resultsmentioning
confidence: 99%